Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2018
DOI: 10.18653/v1/p18-1217
|View full text |Cite
|
Sign up to set email alerts
|

Neural Sparse Topical Coding

Abstract: Topic models with sparsity enhancement have been proven to be effective at learning discriminative and coherent latent topics of short texts, which is critical to many scientific and engineering applications. However, the extensions of these models require carefully tailored graphical models and re-deduced inference algorithms, limiting their variations and applications. We propose a novel sparsityenhanced topic model, Neural Sparse Topical Coding (NSTC) base on a sparsityenhanced topic model called Sparse Top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…The term data mining can be traced back to the 1950s when once large databases were searched using machine learning techniques. Over time, techniques evolved to be associated with data mining let become an integral part of modern database technologies and play an important role in the transition from classical data management Software tools that can directly support management decisions [32].…”
Section: Spatial-temporal Big Data Miningmentioning
confidence: 99%
“…The term data mining can be traced back to the 1950s when once large databases were searched using machine learning techniques. Over time, techniques evolved to be associated with data mining let become an integral part of modern database technologies and play an important role in the transition from classical data management Software tools that can directly support management decisions [32].…”
Section: Spatial-temporal Big Data Miningmentioning
confidence: 99%
“…Feature selection–based software repositories mining: In terms of information extraction, most researchers mainly focus on textual content analysis such as distant supervision methods, topical coding, pattern clustering, and other topic models . However, in SE, most related work used the social features of StackOverflow to mine software repositories for specific software tasks such as code summarization and code search.…”
Section: Related Workmentioning
confidence: 99%
“…They didn't reassumed inference algorithms. [17] Qianqian Xie et al suggested a model named Bayesian Sparse Topical Coding with Poisson Distribution which differs from conventional STMs. While the STMs are the Sparse Topic Models used for understanding and learning semantic meaning of short texts.…”
Section: Related Workmentioning
confidence: 99%